THE INTERNATIONAL POLITICS OF NUCLEAR WEAPONS: A CONSTRUCTIVIST ANALYSIS - Van Wyk, Jo-Ansie; Kinghorn, Linda; Hepburn, Hollie; Payne, Clarence; Sham, Chris (Scientia Militaria - South African Journal of Military Studies, 2011)
Constructivism challenges the prevailing approaches to international relations and security. It attempts to explain, inter alia, how actors acquire their identities, and how these identities shape actors’ material and non-material interests. These constructed identities and interests further define mutually constructed rules, norms and institutions, which enable states and other actors to act accordingly. For constructivists, actors approach social facts in terms of the meaning, significance, value and beliefs these actors ascribe to such facts. Once an actor has constructed the social purpose (i.e. its identity and/or interests) of a particular social fact, the actor ascribes new meaning to this fact. The next step for the actor and others would then be to construct social practices based on mutually constructed norms, rules and institutions to engage with this social fact. States, therefore, could have different identities and varying interests at different times (Barnett, 2005:251-270).